(untitled) (CIPEEX, 2025)
This study aimed to evaluate the spatiotemporal parameters of upper limb (UL) reaching movement in a child with Down syndrome (DS) before and after the application of gametherapy. Three-dimensional motion analysis was performed using the SMART-D 140 system (BTS, Milan, Italy), which enables kinematic evaluation of movement, focusing in this project on upper limb reaching. Gametherapy was applied through a playful memory game (GENIUS) in touchscreen mode. The results suggest that the use of virtual reality, such as the Genius game, can be effective in improving motor performance in individuals with Down syndrome, with potential applications in rehabilitation, although further research is needed in this field.